Calculating the adenoma detection rate in screening colonoscopies only: Is it necessary? Can it be gamed? - Rex, Douglas K.; Ponugoti, Prasanna L. (Endoscopy, 2017)
Background Current recommendations are to calculate the adenoma detection rate (ADR) in screening colonoscopies only. The need to confine the measure to screening has not been established.Methods We retrospectively assessed our quality database for whether calculating ADR from screening, surveillance, and diagnostic colonoscopies (overall ADR) would alter conclusions about the performance of colonoscopists, compared to using an ADR based only on screening colonoscopies. We also prospectively tested the extent to which one physician could corrupt the screening-only ADR by changing the procedure indication after reviewing the examination findings.Results For 15 physicians, screening ADRs differed from the overall ADR by a mean of 2.6 percentage points (range 0 – 6.9 percentage points). Using the overall ADR rather than screening ADR changed the ADR from just below to just above the recommended screening threshold for one physician. In the prospective assessment, a single expert colonoscopist utilized indication gaming in patients with both screening and diagnostic indications and was able to increase his apparent screening-only ADR from 48.4 % to 55.1 %.Conclusions Use of an overall ADR rather than screening-only ADR could simplify ADR measurement, increase the number of examinations available to measure ADR, seldom affect whether a doctor meets recommended ADR thresholds, and eliminate the potential for gaming the ADR by changing the colonoscopy indication.